2015
DOI: 10.3109/09513590.2015.1014785
|View full text |Cite
|
Sign up to set email alerts
|

Obesity adversely impacts the number and maturity of oocytes in conventional IVF not in minimal stimulation IVF

Abstract: Female adiposity might impair oocyte number and maturity in conventional IVF but not in mini-IVF. These data suggest that mild ovarian stimulation might yield healthier oocytes in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 51 publications
2
33
2
Order By: Relevance
“…We observed no differences among BMI categories in the number of follicles retrieved, number of embryos, and number of embryos transferred, which are supported by studies in women with PCOS [22] and without PCOS [19,27,28,[31][32][33][34][35][36], but this is controversial [14,21,29,30,37]. Interestingly, we found that women of normal weight had more follicles of 14-18 mm in diameter than BMI body mass index, hCG human chorionic gonadotropin a P = 0.025, intergroup comparisons using one-way analysis of variance b P = 0.132, intergroup comparisons using one-way analysis of variance c P = 0.314, intergroup comparisons using one-way analysis of variance d P = 0.327, intergroup comparisons using one-way analysis of variance e P = 0.033, intergroup comparisons using one-way analysis of variance f P = 0.084, intergroup comparisons using one-way analysis of variance subjects in other BMI categories, which is supported by a previous observation that PCOS and obesity independently influence oocyte size [38], and that obesity may be associated with poorer-quality oocytes [20,28,30,39,40].…”
Section: Discussionsupporting
confidence: 77%
“…We observed no differences among BMI categories in the number of follicles retrieved, number of embryos, and number of embryos transferred, which are supported by studies in women with PCOS [22] and without PCOS [19,27,28,[31][32][33][34][35][36], but this is controversial [14,21,29,30,37]. Interestingly, we found that women of normal weight had more follicles of 14-18 mm in diameter than BMI body mass index, hCG human chorionic gonadotropin a P = 0.025, intergroup comparisons using one-way analysis of variance b P = 0.132, intergroup comparisons using one-way analysis of variance c P = 0.314, intergroup comparisons using one-way analysis of variance d P = 0.327, intergroup comparisons using one-way analysis of variance e P = 0.033, intergroup comparisons using one-way analysis of variance f P = 0.084, intergroup comparisons using one-way analysis of variance subjects in other BMI categories, which is supported by a previous observation that PCOS and obesity independently influence oocyte size [38], and that obesity may be associated with poorer-quality oocytes [20,28,30,39,40].…”
Section: Discussionsupporting
confidence: 77%
“…We have previously shown in humans that obesity has a negative impact on ovarian function, in particular on genes important in follicular development and ovarian reserve [27,[43][44][45][46][47][48]. In the current study, we did not find an association between BMI and kisspeptin expression in human GCs and we did not find that diet-induced obesity affected ovarian kiss1/kiss1r expression in mice.…”
Section: Discussioncontrasting
confidence: 79%
“…A s the obesity epidemic continues to plague the United States, numerous reports have been published and recommendations made regarding the negative impact of obesity on fertility (1), assisted reproductive technology (ART) effectiveness (2)(3)(4)(5)(6)(7)(8)(9), and pregnancy and obstetric outcomes (5,10). By contrast, limited and conflicting data exist on the impact of being underweight (body mass index [BMI] <18.5 kg/m 2 ), admittedly a less common problem, on fertility and the effectiveness of ART.…”
mentioning
confidence: 99%